2018
DOI: 10.1007/s10902-018-0021-0
|View full text |Cite
|
Sign up to set email alerts
|

Income Inequality, Life Satisfaction Inequality and Trust: A Cross Country Panel Analysis

Abstract: Literature has argued that income inequality crowds out trust. However, whether income inequality makes people less trusting depends on how they perceive income inequality within their personal social context and social cognition. In this paper we therefore conjecture that the relationship of income inequality to trust depends on how income inequality affects inequality of life satisfaction. If life satisfaction inequality is high, distrust is generated among the least happy. This will increase polarization an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 70 publications
2
33
0
1
Order By: Relevance
“…Ngamaba et al 2018), we found no effect of income inequality on SWB. Nevertheless, previous research showed that income inequality has a negative effect on life satisfaction inequality as well as on social trust (Graafland and Lous 2019), which implies that reducing income inequality can be a desirable goal after all (see also Deeming and Jones 2015: 277). Regarding economic growth, the Easterlin-paradoxon states that economic growth only fosters subjective well-being in the short run but not in the long run (10 years or more; Easterlin et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Ngamaba et al 2018), we found no effect of income inequality on SWB. Nevertheless, previous research showed that income inequality has a negative effect on life satisfaction inequality as well as on social trust (Graafland and Lous 2019), which implies that reducing income inequality can be a desirable goal after all (see also Deeming and Jones 2015: 277). Regarding economic growth, the Easterlin-paradoxon states that economic growth only fosters subjective well-being in the short run but not in the long run (10 years or more; Easterlin et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, Indonesia is facing rising and stagnant inequality [43, 44]. Income inequality is a potential factor that may lead to negative effects on wellbeing and/or life satisfaction which then erodes social trust [4547] while social deprivation may lead to depression [48]. Furthermore, for households with lower socio-economic status, community involvement is also low [49], which is a potential cause for low social trust and depression.…”
Section: Discussionmentioning
confidence: 99%
“…These are in general consistent with the findings elsewhere (Sønderskov & Dinesen, 2016). For example, multiple studies showed a robust relation between social trust and subjective well‐being (Glatz & Eder, 2020; Graafland & Lous, 2019; Puntscher et al., 2015). Overall, the findings presented above appear to reinforce the argument that tradition, norms, social participation, social networks, and globalization all are at play.…”
Section: Discussionmentioning
confidence: 99%
“…A positive association between the level of trust and income is also confirmed (Hindman & Yamamoto, 2011; Putnam, 2000). Economic inequality may have a direct negative effect on social trust (Graafland & Lous, 2019; Ivarsflaten & Strømsnes, 2013), and a rise in mean income could be expected to be associated with increased trust (Alesina & La Ferrara, 2002). In the context of South Africa, for example, race differences in trust of neighbors are reduced when personal and neighborhood income is controlled for (Posel & Hinks, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%